IMPROVING THE MATHEMATICAL CREATIVE THINKING ABILITY AND SOFT SKILLS STUDENTS THROUGH VIDEOSCRIBE MULTIMEDIA TEACHING MATERIALS - Kurniati Kurniati; Siti Rohayati (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
This study aims to determine the increase of improving in The Mathematical Creative  Thinking Ability and Soft skills of chemical analysts school students in the Bogor City through  Videoscribe Multimedia Teaching Materials. This research uses the Research & Development (R & D) method by researching and developing multimedia videoscribe learning materials in mathematics learning. The instruments use in this study are videoscribe teaching materials, RPP, pretest and posttest, and soft skills scale questionnaire. The tests use the essay test because they are used to measure high-level abilities. The attitude scale use the Likert Model soft skills scale. The research use two different classes. The first class is an experimental group that obtains learning using videoscribe, while the second class is a control group that does not use videoscribe. The results showed that students who obtained learning using videoscribe media has an increase in creative thinking ability and soft skills better than students who use conventional learning. Data analysis of the increase in the creative thinking ability using 2-way analysis of varians statistical test with interaction, while data analysis for the improvement of soft skills uses the U-Mann Whitney Non-Parametric Test.